Acts - Chung-Kim, Esther, 1973-; Hains, Todd R. (Reformation commentary on Scripture. New Testament ;, 2013)
In this Reformation Commentary on Scripture, we watch as the diverse streams of the Protestant movement converge on the book of Acts. As we return with the Reformers to this vision of Spirit-filled community, we are given a lesson in the nature of biblical reform from those who bore it out for the first time. Authors Esther Chung-Kim and Todd R. Hains present a portrait of the Reformers' views on the contemporary church's faithfulness to its God-given identity and calling. The Reformers approached the narrative account of the early church in the book of Acts from diverse viewpoints. Commentators like John Calvin and the Swiss Reformed Heinrich Bullinger elaborated on the theological implications of the text with a great deal of historical detail. Others like reform-minded Catholic Johann Eck evoked episodes in Acts in response to pressing concerns of the day. Sermons upheld notable characters in Acts such as Peter, Stephen, Paul, Lydia and Apollos as examples of robust faith and of life in Christian community. Anabaptists in their apologetic works focused heavily on the necessity of believer's baptism. The commentators' interactions range from irate disagreement to irenic concord, but all exhort their readers not to dissolve "the holy knot" of the plain history of Christ's works and their lasting fruits. For them, Acts is certainly history, but it cannot be mere history. --From publisher's description.